2015
DOI: 10.1186/s40560-015-0087-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of enteral diet enriched with eicosapentaenoic acid, gamma-linolenic acid, and antioxidants in patients with sepsis-induced acute respiratory distress syndrome

Abstract: BackgroundIn this study, the effects of an enteral diet enriched with eicosapentaenoic acid (EPA), γ-linolenic acid (GLA), and antioxidants were compared with a standard enteral diet in critically ill patients with sepsis-induced acute respiratory distress syndrome (ARDS).MethodsThis study was a single-center, prospective, randomized, single-blind, controlled trial in our Advanced Critical Care Center. Patients were randomized to receive a continuous EPA, GLA, and antioxidant-enriched diet (study group), or an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
93
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(99 citation statements)
references
References 30 publications
4
93
2
Order By: Relevance
“…Three studies [31, 35, 37] required both sepsis and mechanical ventilation for inclusion. One study [32] enrolled ICU and post-anaesthesia care unit (PACU) patients with abdominal sepsis; we abstracted data for the ICU subset only.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three studies [31, 35, 37] required both sepsis and mechanical ventilation for inclusion. One study [32] enrolled ICU and post-anaesthesia care unit (PACU) patients with abdominal sepsis; we abstracted data for the ICU subset only.…”
Section: Resultsmentioning
confidence: 99%
“…Brand-name formulae used included Omegaven [29, 3234, 38, 41], Oxepa [31, 36, 37], Impact [28, 30], and Lipoplus [43]. Available data on the contents of all brand-name intervention and control formulae are given in Additional file 1: Tables S4–S5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To that end, the Medicare data mostly reflect patients who are older than 65 years, limiting the findings of this analysis to older adult patients in the Medicare program. In the example illustrated, the mean age of the patients ranged from 71 to 74 years . Finally, the documented presence of malnutrition was not available across all analyses, because the limited sample size in certain populations did not produce viable results.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies are in favor of the antioxidant treatments, others have demonstrated no effect, while the risk for adverse outcomes due to pro-oxidant phenomena has also been stressed [15,16,17]. Noteworthy, even the relevant reviews and meta-analyses did not result in a universally accepted takehome message [18,19,20,21].…”
Section: Introductionmentioning
confidence: 99%